A bionic approach for heat generation and latent heat storage inspired by the polar bear. (1st February 2019) - August, Anastasia; Kneer, Aron; Reiter, Andreas; Wirtz, Michael; Sarsour, Jamal; Stegmaier, Thomas; Barbe, Stéphan; Gresser, Götz T.; Nestler, Britta
Abstract: The roof of the polar bear building (Fig. 1 ) is a prototype of a textile membrane structure, which can be used to absorb solar energy. The inspiration for this technology, especially the roof, made from a specific sandwich structure of knitted fabrics, has been provided by the coat of the polar bear. This bionic approach allows the absorption of solar energy, which can be transported by means of air flow, through forced convection. Hereby, the knitted fabrics are designed as a porous channel, through which air can flow, and which at the same time is translucent for solar radiation. The solar energy is absorbed by a subjacent black foil, which represents the skin of the polar bear. Its fur, which distributes light effectively and acts as thermal insulation, is modelled by knitted fabrics. The polar bear building has been installed in Denkendorf, near Stuttgart, at the Institute of Textile Technology and Process Engineering, Denkendorf (DITF Denkendorf, Germany). Within a follow-up research project, a latent heat storage system is developed, which is to be integrated into the textile roof. A thermal storage system of this kind can help to store energy, which is to be used at a later time. In the field of low-temperature applications, sensible storage materials like water are usually applied. Naturally, the storage density is limited by the heat capacity of the selected fluid. Within the presented approach, a phase change material (PCM) is chosen as an integrated (local) storage system. The advantage of a PCM is that an additional storage capacity - the phase change energy - can be exploited. In this work, we show that the further developed solar absorber system can be extended by a latent heat storage system, which uses paraffin wax as a phase change material. To qualify the described combination, an experimental facility has been set up, and simulation studies have been performed using a fully resolved virtual model of the integrated storage device. The results of the experimental, analytical and numerical studies, including radiation, convection and phase transformation, show that heat can be buffered for some hours within the locally integrated storage systems. We also show that the integration of a storage system into a textile roof is limited, because of the resulting mass which is necessary to store energy during a whole sunny day. The experimental results from the polar bear building provide the right boundary conditions for all performed simulations. The simulations are performed using both the software suite PACE3D from the Institute of Digital Materials and the commercial solver STAR-CCM+. Finally, it is demonstrated that the efficiency of the latent heat storage system can be improved by elaborating a different geometric design of the storage containers. Highlights: We present a heat production and storage system made by spacer fabrics and wax. We imitate in this system the functionality of polar bear's fur and fat. Spacer fabris is to absorb the solar energy and pcm wax is to store it. Experiments and simulations of heat transport and phase transition are performed.